Multidimensional Community Empowerment through Health, Education, and Digital Economy Interventions in Juwiring Village: Pemberdayaan Masyarakat Multidimensi melalui Intervensi Kesehatan, Pendidikan, dan Ekonomi Digital di Desa Juwiring - Muhammad Saiq Arridlo; Khoirun Nisa; Mila Rosalia; Syarifatun Ni’mah; Salma Syahidah; Muhamad Asifaq; Dewi Latifah Qolbi; Fanesya Rahma Julita; Dwi Nur Ningsih; Amelia Putri Sulistya; Renaldi; Istiqomah (Yayasan Cerdas Pedia Indonesia, 2025)
This study analyzes the implementation of a multidimensional community empowerment program through the Thematic Community Service (KKN-T) initiative conducted by Alma Ata University students in Juwiring Village, Kendal Regency, from August 1 to September 26, 2024. The program addressed the complex issue of stunting and socio-economic challenges through integrated interventions across three sectors: health, education, and digital economy. Health interventions included balanced nutrition education for mothers with stunted children, Clean and Healthy Living Behavior (PHBS) promotion in kindergarten, and Posyandu assistance. Education programs encompassed anti-bullying socialization and tutoring services for elementary students. Digital economy initiatives focused on UMKM digitization through branding, Google Maps registration, and website development for local institutions. The participatory community service approach successfully increased community awareness about stunting prevention, enhanced digital literacy among local entrepreneurs, and strengthened the educational ecosystem. This integrated model demonstrates the effectiveness of multisectoral interventions in addressing rural development challenges and creating sustainable community assets.